PENGARUH RATIONAL EMOTIVE BEHAVIOR THERAPY (REBT) TERHADAP PENURUNAN SIMPTOM GENERALIZED ANXIETY DISORDER (GAD) - Srifianti, Srifianti (Jurnal Psikologi : Media Ilmiah Psikologi, 2018)
AbstractGeneralized anxiety disorder (GAD) is one of the most debilitating mental disorders, it was a psychological disorder characterized by chronic anxiety and its floating (free floating anxiety)(Barlow, 2001). GAD sufferers always feel the tension throughout his life to make him suffer, consequently daily activities - the sufferer becomes limited and inefficient. They are always worried about the various situations that they are facing in their lives. GAD sufferers are mostly women and is more common in early adulthood is a time where this time looking for a job, looking for spouse and being family. GAD also disorders usually appear in individuals who experience many stressful episode in life. That they lived as the pressure that can lead to emotional disorders such as anxiety. Anxiety disorder in the form of fear of bad luck, felt the pinch, both physical strain and psychological. According to Ellis (Jones & Nelson, 2011) between the mind and emotions have a strong bond. When a person thinks and emotionless negative then he tends to talk things - things that are negative to itself (self-talk) is then internalized to him, giving rise to irational beliefs which affect the behavior. Anxiety experienced by patients GAD started thinking - negative thoughts that accompanied the belief - often negative beliefs towards various problems faced in life. To help people with GAD in overcoming its irrational beliefs need to be an effective approach to cognitive one of them is the Rational Emotive Behavior Therapy (REBT). REBT emphasis on how the mind affects the emotional feelings or someone who will form the individual to behave. The emergence of irrational thoughts later on in the process of REBT therapy will be transformed into rational thoughts so that the client / patient is able to develop themselves more effectively, and this is the goal of REBT therapy (Neenan in Palmer, 2011). This study aims to find empirical data about how much therapy REBT giving effect to decrease symptoms of Generalized Anxiety Disorder (GAD) GAD, so patients can live their lives in a more effective and develop themselves better. This study using pre-experimental design (one group pretest-post test design) with a number of research 2 subjects. Measuring instruments used to measure the Generalized Anxiety Disorder (GAD) is to use a measurement tool developed by researchers based on the concept of PPDGJ III (Guidelines for the Classification of Mental Disorder Diagnosis) and measurement tools supporting modified consisting of observations and interviews.Based on the calculation of descriptive statistics, the data can be obtained that there is a decrease symptoms of Generalized Anxiety Disorder (GAD) from before and after the therapy REBT is equal to 10.68%. Aspects of GAD symptoms most of the changes are aspects of motor tension by 21.4%. This shows the influence of Rational Emotive Behavior Therapy (REBT) to symptoms of Generalized Anxiety Disorder (GAD). Keywords: rational emotive behavior therapy, anxiety AbstrakGeneralized Anxiety Disorder (GAD) adalah gangguan psikologis yang ditandai dengan kecemasan yang kronis dan sifatnya mengambang (free floating anxiety)(Barlow 2001). Penderita GAD selalu merasakan ketegangan sepanjang hidupnya yang dapat membuatnya menderita, akibatnya aktivitas sehari – hari penderitanya menjadi terbatas dan tidak efisien. Mereka selalu mencemaskan berbagai situasi yang sedang mereka hadapi dalam kehidupannya. Penderita GAD kebanyakan adalah wanita dan lebih banyak terjadi pada masa dewasa awal dimana masa ini merupakan masa mencari pekerjaan, mencari pasangan hidup dan berkeluarga. Gangguan GAD juga biasanya muncul pada individu yang merasakan banyaknya peristiwa stress dalam kehidupannya. Hal ini mereka hayati sebagai tekanan yang dapat menyebabkan gangguan emosional yang berupa kecemasan. Menurut Ellis (Jones&Nelson, 2011) antara pikiran dan emosi memiliki keterkaitan yang erat. Ketika seseorang berpikir dan beremosi negatif maka ia cenderung berbicara hal – hal yang bersifat negatif kepada dirinya sendiri (self talk) yang kemudian diinternalisasikan kepada dirinya sehingga menimbulkan irational beliefs yang berpengaruh kepada perilakunya. Kecemasan yang dialami oleh pasien GAD berawal dari pemikiran negatif yang disertai adanya keyakinan–keyakinan negatif pula terhadap berbagai permasalahan yang dihadapi dalam kehidupannya. Untuk membantu penderita GAD dalam mengatasi keyakinan irrasional yang dimilikinya perlu dilakukan pendekatan kognitif yang efektif yaitu Rational Emotive Behavior Therapy (REBT). Penekanan REBT yakni pada cara pikiran mempengaruhi perasaan atau emosional seseorang yang akan membentuk individu dalam berperilaku. Munculnya pikiran-pikiran irrasional nantinya di dalam proses terapi REBT akan diubah menjadi pikiran-pikiran yang rasional sehingga klien mampu mengembangkan dirinya secara lebih efektif, dan inilah merupakan tujuan dari terapi REBT (Neenan dalam Palmer, 2011).Penelitian ini bertujuan untuk menemukan data empiris tentang seberapa besar pemberian terapi REBT memberi pengaruh terhadap penurunan simptom Generalized Anxiety Disorder (GAD) sehingga penderita GAD dalam menjalani kehidupannya dapat lebih efektif dan mengembangkan dirinya lebih baik.Design yang digunakan dalam penelitian ini adalah pre-experimental design yaitu the one group pretest-post test design dengan jumlah subjek penelitian 2 orang. Alat ukur yang digunakan untuk mengukur simptom Generalized Anxiety Disorder adalah dengan menggunakan alat ukur yang disusun oleh peneliti berdasarkan konsep PPDGJ III (Pedoman Penggolongan Diagnosis Gangguan Jiwa III) serta alat ukur penunjang yang terdiri dari observasi dan wawancara. Berdasarkan perhitungan statistik deskriptif, dapat diperoleh data bahwa ada penurunan simptom Generalized Anxiety Disorder (GAD) dari sebelum dan sesudah diberikan terapi REBT yaitu sebesar 10,68%. Ini menunjukkan adanya pengaruh Rational Emotive Behavior Therapy (REBT) terhadap simptom Generalized Anxiety Disorder (GAD). Kata kunci :terapi rational emotif, kecemasan